2013
DOI: 10.1111/mve.12029
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and longevity of newly developed catnip oil microcapsules against stable fly oviposition and larval growth

Abstract: The stable fly, Stomoxys calcitrans (Diptera: Muscidae), is one of the most important pests of cattle and costs U.S. cattle producers billions of dollars in losses annually. In this study, the efficacy of catnip oil encapsulated in gelatin in oviposition deterrence and larval growth inhibition in stable flies was examined under laboratory conditions. More than 98% inhibition of stable fly larval growth and female oviposition was observed in larval and oviposition media treated with encapsulated catnip oil (0.5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 27 publications
0
13
0
Order By: Relevance
“…The research done by Zenasni et al (2008) shows that Escherichia coli and Staphylococcus aureus are more sensitive than Pseudomonas aeruginosa to essential oil from the Nepeta genus (p<0.001). The research made by Zhu et al (2014), found more than 98% inhibition of stable fly larval Stomoxys calcitrans (Diptera: Muscidae) growth and female oviposition was observed in larval and oviposition media treated with encapsulated catnip oil (0.5μg). Further, dose-response tests showed that as little as 0.1 μg of encapsulated catnip oil provided more than 85% oviposition deterrence.…”
Section: Results and Disscusionmentioning
confidence: 99%
See 1 more Smart Citation
“…The research done by Zenasni et al (2008) shows that Escherichia coli and Staphylococcus aureus are more sensitive than Pseudomonas aeruginosa to essential oil from the Nepeta genus (p<0.001). The research made by Zhu et al (2014), found more than 98% inhibition of stable fly larval Stomoxys calcitrans (Diptera: Muscidae) growth and female oviposition was observed in larval and oviposition media treated with encapsulated catnip oil (0.5μg). Further, dose-response tests showed that as little as 0.1 μg of encapsulated catnip oil provided more than 85% oviposition deterrence.…”
Section: Results and Disscusionmentioning
confidence: 99%
“…Encapsulated catnip oil also exhibited antibacterial activity, supporting the hypothesis that its inhibition of larval growth may be based on its killing of the bacteria on which larvae feed. The use of encapsulated catnip oil can provide an alternative control strategy for stable fly management (Zenasni et al, 2008;Bandh et al, 2011;Zhu et al, 2014).…”
Section: Results and Disscusionmentioning
confidence: 99%
“…Several essential oils (plant-derived) have been used as repellents against stable flies (e.g., catnip, peppermint, eucalyptus and lemongrass) [127][128][129][130][131][132] but again the repellency only lasts 1-2 d. A repellent oil combination of sunflower (95%), geranium (2.5%) and lemongrass (2.5%) applied to dairy cattle reduced both stable flies on the animals and fly defensive behaviors [133]. DEET has been added to numerous products for fly control to improve the repellency of biting flies.…”
Section: Repellents On Livestockmentioning
confidence: 99%
“…Microencapsulation works by coating the repellent molecules with a film to produce small capsules. The resulting formulation results in a significant reduction in evaporative loss of the repellent whilst maintaining a consistent release rate (Solomon et al 2012), although environmental conditions can influence the release rate depending on the capsule structure and material used (Zhu et al 2014). Compounds trialled as repellent additives include synthetic musks such as vanillin (4-hydroxy-3-methyoxy-benzaldehyde): a 1:3 ratio of DEET to vanillin increased the protection time against Aedes aegypti Linnaeus by 176% (Khan et al 1975).…”
Section: Key Considerations For Repellentsmentioning
confidence: 99%